Mesenchymal Stromal Cell Derived Membrane Particles Are Internalized by Macrophages and Endothelial Cells Through Receptor-Mediated Endocytosis and Phagocytosis - da Costa Gonçalves, Fabiany; Korevaar, Sander S.; Ortiz Virumbrales, Maitane; Baan, Carla C.; Reinders, Marlies E. J.; Merino, Ana; Lombardo, Eleuterio; Hoogduijn, Martin J. (Frontiers in Immunology, 2021)
Mesenchymal stromal cells (MSC) are a promising therapy for inflammatory diseases. However, MSC are large and become trapped in the lungs after intravenous infusion, where they have a short survival time. To steer MSC immunoregulatory therapy beyond the lungs, we generated nm-sized particles from MSC membranes (membrane particles, MP), which have immunomodulatory properties, and investigated their internalization and mode of interaction in macrophages subtypes and human umbilical vein endothelial cells (HUVEC) under control and inflammatory conditions. We found that macrophages and HUVEC take up MP in a dose, time, and temperature-dependent manner. Specific inhibitors for endocytotic pathways revealed that MP internalization depends on heparan sulfate proteoglycan-, dynamin-, and clathrin-mediated endocytosis but does not involve caveolin-mediated endocytosis. MP uptake also involved the actin cytoskeleton and phosphoinositide 3-kinase, which are implicated in macropinocytosis and phagocytosis. Anti-inflammatory M2 macrophages take up more MP than pro-inflammatory M1 macrophages. In contrast, inflammatory conditions did not affect the MP uptake by HUVEC. Moreover, MP induced both anti- and pro-inflammatory responses in macrophages and HUVEC by affecting gene expression and cell surface proteins. Our findings on the mechanisms of uptake of MP under different conditions help the development of target-cell specific MP therapy to modulate immune responses.